Characterization of a Temperature-Sensitive Fiber Mutant of Type 5 Adenovirus and Effect of the Mutation on Virion Assembly - Chee-Sheung, Cecilia Cheng (1982)
A temperature-sensitive, fiber-minus mutant of type 5 adenovirus, H5ts142, was biochemically and genetically characterized. Genetic studies revealed that H5ts142 was a member of one of the three apparent fiber complementation groups which were detected owing to intracistronic complementation. Recombination analyses showed that it occupied a unique locus at the right end of the adenovirus genetic map. At the nonpermissive temperature, the mutant made stable polypeptides, but they were not glycosylated like wild-type fiber polypeptides. Sedimentation studies of extracts of H5ts142-infected cells cultured and labeled at 39.5°C indicated that a limited number of the fiber polypeptides made at the nonpermissive temperature could assemble into a form having a sedimentation value of 6S (i.e., similar to the trimeric wild-type fiber), but that this 6S structure was not immunologically reactive. When H5ts142-infected cells were shifted to the permissive temperature, 32°C, fiber polypeptides synthesized at 39.5°C were as capable of being assembled into virions as fibers synthesized in wild type-infected cells; de novo protein synthesis was not required to allow this virion assembly. In H5ts142-infected cells incubated at 39.5°C, viral proteins accumulated and aggregated into particles having physical characteristics of empty capsids. These particles did not contain DNA or its associated core proteins. However, when the infected culture was shifted to 32°C, DNA appeared to enter the empty particles and complete virions developed. The intermediate particles obtained had the morphology of adenoviruses, but they contained less than unit-length viral genomes as measured by their buoyant density in a CsCl density gradient and the size of their DNA as determined in both neutral and alkaline sucrose gradients. The reduced size of the intermediate particle DNA was demonstrated to be the result of incompletely packaged DNA molecules being fragmented during the preparative procedures. Hybridization of labeled DNA extracted from the intermediate particles to filters containing restriction fragments of the adenovirus genome indicated that the molecular left end of the viral genome preferentially entered these particles.